Map of perforators of the posterior tibial artery and peroneal artery using handheld doppler ultrasound evaluating clinical outcome of perforator flaps which cover soft tissue defects of the lower leg and foot - Le, Hong Phuc; Le, Nghi Thanh Nhan (Tạp chí Y Dược Huế, 2022)
Background: Soft tissue defects of the lower leg and foot are complicated injuries with numerous causes including trauma, ulcers, and Gout. Widespread treatment of these defects has been effectively applied with perforator flaps of the peroneal artery and posterior tibial artery. Objectives: 1. To construct a map of the perforators of the peroneal artery and posterior tibial artery using a handheld Doppler ultrasound. 2. To evaluate the clinical outcome of perforator flaps to cover soft tissue defects in the lower leg and foot. Materials and method: Cross-sectional study of 34 volunteers with no previous history of vascular diseases and the prospective study of 31 patients with soft tissue defects treated with peroneal artery perforator flap and posterior tibial artery perforator flap. Results: There are, on average, 4.7 peroneal perforating arteries. From the lateral malleolus to the fibula’s head, the percentage of perforating arteries in the 2/10 and 6/10 segments is 85.3% and 97%, respectively. In the 2-3/10 segment, 94.1% have perforator arteries. There are, on average, 3.3 posterior tibial artery perforators. From the medial malleolus to the medial tibial plateau, it was found that 100% of volunteers had perforating arteries in the 3-4/10 segments and 61.7% in the 5/10 segment. Evaluation of postoperative results in 31 patients: 77.49% showed the right flap. The most common complications were edge necrosis (12.9%), partial necrosis (6.44%), and infection (3.23%). The donor sites showed good survival in 96.4% of patients, while partial necrosis resulted in 3.6%. A follow-up examination revealed that 90.32% of flaps had a good result, 9.68% had an average result, and no poor results were shown. 100% of donor sites had good results. Conclusion: An average of 4.7 perforators of the peroneal artery is detected by handheld Doppler ultrasound. Also, there are 1-2 relatively constant perforators in segments 2/10 and 5-6/10 from the lateral malleolus. On average, there are 3.3 perforators of the posterior tibial artery, primarily in the 3-4/10 and 5/10 segments proximally from the medial malleolus. 90.32% of the flap had good results.